The lncRNA APOLO and the transcription factor WRKY42 target common cell wall EXTENSIN encoding genes to trigger root hair cell elongation. (3rd August 2021) - Pacheco, Javier Martínez; Mansilla, Natanael; Moison, Michaël; Lucero, Leandro; Gabarain, Victoria Berdion; Ariel, Federico; Estevez, José M.
ABSTRACT: Plant long noncoding RNAs (lncRNAs) are key chromatin dynamics regulators, directing the transcriptional programs driving a wide variety of developmental outputs. Recently, we uncovered how the lncRNA AUXIN REGULATED PROMOTER LOOP ( APOLO ) directly recognizes the locus encoding the root hair (RH) master regulator ROOT HAIR DEFECTIVE 6 ( RHD6 ) modulating its transcriptional activation and leading to low temperature-induced RH elongation. We further demonstrated that APOLO interacts with the transcription factor WRKY42 in a novel ribonucleoprotein complex shaping RHD6 epigenetic environment and integrating signals governing RH growth and development. In this work, we expand this model showing that APOLO is able to bind and positively control the expression of several cell wall EXTENSIN (EXT) encoding genes, including EXT3, a key regulator for RH growth. Interestingly, EXT3 emerged as a novel common target of APOLO and WRKY42. Furthermore, we showed that the ROS homeostasis-related gene NADPH OXIDASE C (NOXC) is deregulated upon APOLO overexpression, likely through the RHD6-RSL4 pathway, and that NOXC is required for low temperature-dependent enhancement of RH growth. Collectively, our results uncover an intricate regulatory network involving the APOLO /WRKY42 hub in the control of master and effector genes during RH development.